Galerie Michael Haas 1988 : Aus den Beständen der Galerie. - Galerie Michael Haas, Berlin (Berlin : Galerie Michael Haas, 1988)
Appel, Karel ; Averbuch, Ilan ; Basquiat, Jean-Michel ; Baumeister, Willi ; Brandl, Herbert ; Brands, Eugène ; Brüning, Peter ; Brus, Günter ; Chaissac, Gaston ; Chia, Sandro ; Combas, Robert ; Cucchi, Enzo ; Dix, Otto ; Dubuffet, Jean ; Fischer, Lothar ; Grabmayr, Franz ; Grosz, George ; Hölzel, Adolf ; Jawlensky, Alexej von ; Jorn, Asger ; Knöller, Paco ; Lehmbruck, Wilhelm ; Michaux, Henri ; Morgner, Wilhelm ; Mosbacher, Alois ; Mueller, Otto ; Munch, Edvard ; Nay, Ernst Wilhelm ; Nicholson, Ben ; Nolde, Emil ; Paladino, Mimmo ; Partenheimer, Jürgen ; Rainer, Arnulf ; Richter, Gerhard ; Schulz-Rumpold, Volkmar ; Schumacher, Emil ; Soutter, Louis ; Sturm, Helmut ; Wallis, Alfred ; Werefkin, Marianne von ; Wilson, Scottie ; Zimmer, Hans-Peter
biog. per kunstenaar
Duits
Aus den Beständen der Galerie 1988, Galerie Michael Haas Berlin, 18.03 - 13.05.1988
boek